Government's 10 year plan for transport what next?. (Thomas Telford, 2001)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a joint seminar with the Institute of Logistics and Institution of Highways and Transportation held in London on 19 February 2001.
Keywords: Transportation and state -- Great Britain -- Congresses.; elektronické knihy; electronic books